Transmission probability of COVID-19 variants in an egg washing facility - Signey, Donnel Paulo G.
This study investigated the probability of COVID-19 transmission of the Wuhan, Delta, and Omicron variants for an adopted egg washing facility using two modes of measurement namely, multi-method simulation (Grigoryev, 2018) and the adopted Wells-Riley equation (Riley et al.,1978) formula. Utilizing multi-method simulation modeling, a functional model of an adopted egg washing facility was created and the risk of transmission was measured using physical distance parameters. In the adopted Wells-Riley equation, the ventilation rate, average breathing rate, and the use of face masks were utilized to calculate the probability of COVID-19 transmission. Using the multi-method simulation, the Omicron variant was found to be 1.73x more transmissible than the Delta and Wuhan variant, both sharing the same transmissibility. Based on the Wells-Riley equation, the Delta variant was calculated to be 1.9x more transmissible than the Wuhan variant and the Omicron variant was 1.3x more transmissible than the Delta variant. The Wells-Riley equation was found to be the better mode of measurement as it generated more consistent results with present COVID-19 transmission similar to that reported by Liu and Rocklov (2022). Further studies using the Wells-Riley equation may be done to compare observations from simulation models to the actual adopted egg washing facility in terms of COVID-19 transmission. Future research on the effects of larger workspaces, increased number of personnel, and personnel vaccination status on the likelihood of COVID-19 transmission may also be investigated using the Wells-Riley equation.